Formononetin Protects LPS-Induced Mastitis Through Suppressing Inflammation and Enhancing Blood-Milk Barrier Integrity via AhR-Induced Src Inactivation - Xiang, Kaihe; Shen, Peng; Gao, Ziyang; Liu, Zhuoyu; Hu, Xiaoyu; Liu, Bin; Fu, Yunhe (Frontiers in Immunology, 2022)
It is commonly accepted that inflammation plays a critical role in the pathogenesis of mastitis. Formononetin (FOR), a flavonoid derived from Radix Astragali, has been reported to have anti-inflammatory and anti-oxidative effects. Therefore, we investigated whether FOR had protective effects on LPS-induced mastitis in mice. The mice were exposed to LPS 24 h to induce mastitis model. FOR was administrated 1 h before LPS treatment. The results showed that LPS-induced mammary histological injury was inhibited by FOR. FOR significantly inhibited LPS-induced MPO activity, as well as TNF-α and IL-1ß production. FOR also enhanced the integrity of blood-milk barrier. In vitro, FOR significantly attenuated LPS-induced NF-κB activation and inflammatory cytokine production. FOR also increased the expression of tight junction protein. Furthermore, FOR increased the expression of AhR in a dose-dependent manner. And FOR significantly inhibited LPS-induced phosphorylation level of Src. In addition, AhR antagonist CH223191 reversed the inhibition of FOR on Src expression. And the inhibition of FOR on NF-κB activation and inflammatory cytokine production were reversed by AhR antagonist CH223191. In conclusion, FOR had protective effects against LPS-induced mastitis via suppressing inflammation and enhancing blood-milk barrier integrity via AhR-induced Src inactivation.